Few substitutions affect the bioluminescence spectra of Phrixotrix (Coleoptera: Phengodidae) luciferases: a site-directed mutagenesis survey - Viviani, Vadim R. [UNESP]; Arnoldi, Frederico G.C. [UNESP]; Ogawa, Florisbela T. [UNESP]; Brochetto-Braga, M. [UNESP] (Wiley, 2007)
Phrixotrix (railroad worm) luciferases produce bioluminescence in the green and red regions of the spectrum, depending on the location of the lanterns, and are the only luciferases naturally producing red bioluminescence. Comparison of the luciferase sequences showed a set of substitutions that could be involved in bioluminescence colour determination: (a) unique substitutions in the red luciferase replacing otherwise invariant residues; (b) conserved basic residues in the green-yellow emitting luciferases; and (c) an additional R353 residue in red-emitting luciferase (Viviani et al., 1999). To investigate whether these sites have a functional role in bioluminescence colour determination, we performed a site-directed mutagenesis. Natural substitutions in the region 220-344 and residues in the putative luciferin-binding site were also investigated. With the exception of the previously identified substitution of R215 and T226 (Viviani et al., 2002), which display dramatic red-shift effects on the spectrum of green-yellow-emitting luciferases, only a few substitutions had a moderate effect on the spectrum of the green-emitting luciferase. In contrast, no single substitution affected the spectrum of the red-emitting luciferase. The results suggest that the identity of the active site residues is not so critical for determining red bioluminescence in PxRE luciferase. Rather, the conformation assumed during the emitting step could be critical to set up proper interactions with excited oxyluciferin. Copyright ©2007 John Wiley & Sons, Ltd.
Keywords: Bioluminescence; Click beetles; Fireflies; Luciferases; Phrixotrix; Railroad worms; indole derivative; luciferase; oxyluciferin; photoprotein; pyrazine derivative; unclassified drug; amino acid substitution; binding site; chemistry; color; genetics; luminescence; site directed mutagenesis; spectroscopy; Amino Acid Substitution; Binding Sites; Color; Indoles; Luminescent Measurements; Luminescent Proteins; Mutagenesis, Site-Directed; Pyrazines; Spectrum Analysis; Coleoptera; Elateridae; Lampyridae; Phengodidae